A multi-parameter model for stiffness prediction of composite laminates with out-of-plane ply waviness. (1st February 2018) - Zhu, Jun; Wang, Jihui; Ni, Aiqing; Guo, Wantao; Li, Xiang; Wu, Yibo
Graphical abstract: Highlights: A multi-parameter model with waviness defect and material properties is developed. The 3D stiffness of the wavy composite laminates are investigated systematically. The negative in-plane Poisson's ratio is found for CFRP with ply waviness. The effects of waviness defect on composite laminates are determined quantitatively. Abstract: In this paper, an analytical multi-parameter model based on the classical lamination theory (CLT) is developed and the study of the stiffness response for unidirectional composite laminates with out-of-plane ply waviness is followed. A range of parameters associated with the waviness defect, including the waviness geometry, the fiber off-axis angle, the extent of wavy region and the waviness pattern, are incorporated into the analytical model. The fiber volume fraction and the type of reinforcement are also taken into account in the parametric analysis. The three-dimensional stiffness parameters of thick wavy laminates are investigated systematically for different cases. An observation of the negative in-plane Poisson's ratios for wavy laminated composites reinforced with carbon fibers is presented under the given assumptions of CLT. This phenomenon provides a possible, new technique to design the auxetic materials. The modeling approach provides an effective procedure to quantify the effects of ply waviness on the stiffness of composite laminates.